Right n-derivations in prime near – rings - H. Majeed, Abdul Rahman; F. Adhab, Enaam. (Al-Qadisiyah Journal of Pure Science, 2017)
In this paper, we introduce the notions of right derivations and right n-derivations in near-ring N and investigate prime near – rings with right n-derivations satisfying certain differential identities